2003
DOI: 10.1002/ijc.11350
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and risk factors for cervical cancer in Chennai, India: A case‐control study

Abstract: To evaluate the role of human papillomavirus (HPV) and other risk factors in the aetiology of invasive cervical carcinoma (ICC), we conducted a hospital-based case-control study in Chennai, Southern India. A total of 205 ICC cases (including 12 adenocarcinomas) and 213 frequency agematched control women were included. HPV DNA in cervical cells was evaluated by means of a polymerase chainreaction assay. Odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were computed by means of unconditional mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
111
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(138 citation statements)
references
References 28 publications
(41 reference statements)
23
111
2
1
Order By: Relevance
“…3 Overall, these findings suggest that the distribution of HPV types in CC from north Africa resembles more closely the distribution found in similar studies in Europe and North America than that found in the rest of the African continent, where HPV 16 accounts for less that 50% of HPV positivity. 12 As in most previous work, 7,13 infection with multiple HPV types did not confer an increased risk compared to single-type infection.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…3 Overall, these findings suggest that the distribution of HPV types in CC from north Africa resembles more closely the distribution found in similar studies in Europe and North America than that found in the rest of the African continent, where HPV 16 accounts for less that 50% of HPV positivity. 12 As in most previous work, 7,13 infection with multiple HPV types did not confer an increased risk compared to single-type infection.…”
Section: Discussionmentioning
confidence: 56%
“…While 90% of CC cases had never had a Pap smear, 1/3 of control women did report having had at least one (i.e., a nonnegligible proportion compared to many developing countries). 13 With respect to indicators of sexual habits, the association with age at first sexual intercourse and number of sexual partners was found as expected, but risk trends did not reach statistical significance. Only 10% of CC cases and 5% of control women reported 3 lifetime sexual partners or more.…”
Section: Discussionmentioning
confidence: 57%
“…The results from a case control study in Chennai showed that high parity (>4 vs. ≤ 2 births) was associated with invasive cervical cancer (OR=7.3) after restricting the analysis to HPV positive women (Franceschi et al, 2003). Birth interval or the rapidity of multiple pregnancies also has an independent influence on the risk for cervical cancer (Mukherjee et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…All the present study subjects were married, 85% of them being sexually active and younger than 35 years of age (this age-group is known to have high incidence of transient HPV infection), 84% reported early age of marriage/sexual intercourse (16e22 years, median 19 years), more than 95% had one or more pregnancies (range 1e6, median-2), younger age at child birth, etc., that may influence HPV infection risk significantly. 2,10,12 We acknowledge that due to the cross-sectional nature of the present study, we could not resolve the issue of transient infection. Nevertheless, considering the risk factors, HPV prevalence differs considerably from previous studies and is not generalizable to other populations.…”
Section: Discussionmentioning
confidence: 89%
“…2,9 Same is true for HPV also, as its prevalence varies greatly across India. 2,4,10 Among asymptomatic population, normally 10e12% to as high as 64% HPV prevalence has been reported from certain parts of India. 2,11 Moreover, HPV 16 is predominant in India, detectable in 22% of general population, while ranging from w14 to 88% in cervical cancer population.…”
Section: Discussionmentioning
confidence: 99%